Pemberian Ekstrak Rumput Kebar (Biophytum petersianum Klotzsh) Dapat Meningkatkan Berat Testis Mencit Model Diabetes Mellitus - Yohana Djurumana; Reny I’tishom; Bambang Purwanto (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: In addition to the influence of diabetes on male reproduction lowers testosterone levels of FSH and LH, the second number of hormones is reduced will interfere with the process of spermatogenesis. If the spermatogenesis process is interrupted then the number of germ cells decreases, this will cause a decrease in the weight of the testes. Objective: To analyze the effect of extract grass administration to the weight of the testicles diabetes Mellitus mice between the treatment group and the control. Methods: The research used DM male mice which is divided into 5 groups each consisting of 6 mice. Day 1 till day 5 all STZ-induced groups. On the 11th day to the 45th day, the control group (K +) was given metformin 2mg/head/day. The control group (K-) was given CMC-Na 1%. Group P1, P2 and P3 was given Kebar grass with dose of 67, 5mg/day, 135mg/kg/day, and 270mg/kg/day and metformin 2mg/head/day. The 46th was done with the release and sampling of the right and left testicles. Testicular weighing used analytic scales 0.001gram. Results: Statistical tests showed that there was a discrepancy in the p-value = 0.000 (0.05) on testicular weight. Conclusion: Increased testicular weight model of diabetes mellitus that gets the grass extractions of Kebar. Keywords: Kebar grass extract; testicular weight; diabetes mellitus ABSTRAK Latar belakang: Pengaruh diabetes mellitus terhadap reproduksi pria menurunkan kadar testosterone yaitu FSH dan LH, jumlah ke dua hormone tersebut berkurang maka akan mengganggu roses spermatogenesis. Proses spermatogenesis terganggu maka jumlah sel germinal mengalami penurunan, hal ini akan menyababkan berat testis menurun. Tujuan: menganalisisi pengaruh pemberian ekstrak rumput kebar terhadap berat testis mencit model diabetes mellitus antara kelompok perlakuan dan kontrol. Metode: penelitian menggunakan mencit DM yang dibagi menjadi lima kelompok setiap kelompok terdiri dari 6 ekor mencit. Hari ke 1 sampai hari ke 5 semua kelompok diinduksi STZ. Hari ke 11 sampai hari ke 45 kelompok kontrol (K+) disonde metformin 2mg/ekor/hari. Kelompok kontrol (K-) disonde CMC Na 1%. Kelompok P1,P2 dan P3 disonde ekstrak rumput kebar dengan dosis, 67,5mg/kgBB/hari, 135mg/kgBB/hari, 270mg/kgBB/hari dan metformin 2mg/ekor/hari. Hari ke 46 dilakukan pembedahan dan pengambilan sampel testis kanan dan kiri dan Penimbangan berat testis mencit menggunakan timbangan analitik dengan skala 0,001 gram. Hasil: uji statistik menunjukkan terdapat perbedaan bermakna dengan nilai p= 0,000 (p